2021
DOI: 10.1108/ijppm-11-2020-0601
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of employee creative behavior in the UAE public sector

Abstract: PurposeService levels between public organizations in the United Arab Emirates (UAE) differ and fluctuate. Service levels were found to increase with the level of employee creative behavior (ECB), which is currently a focal point in organizational policies by the federal UAE government. While the literature presents an ample array of determinants of ECB, local context typically influences which determinants provide more leverage than others. Therefore, this research aims to present a customized ranking of dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…The researcher found a positive and significant relationship between HCWS and employee well-being. HCWS is considered a set of HR practices that help to encourage employee commitment to an organization (Al Hosani et al , 2021). The more HR measures are in organizations, the more controlled the work environment might feel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher found a positive and significant relationship between HCWS and employee well-being. HCWS is considered a set of HR practices that help to encourage employee commitment to an organization (Al Hosani et al , 2021). The more HR measures are in organizations, the more controlled the work environment might feel.…”
Section: Discussionmentioning
confidence: 99%
“…They show that most employees are satisfied with their current jobs, primarily citing nonfinancial factors such as a positive work environment and work that challenges them as individuals. On the other hand, a study shows that many public sector employees feel they cannot fulfil their individual potential, build relationships with colleagues and find purpose in their work (Al Hosani, 2023). Previous studies conducted in the United Arab Emirates (UAE) focused on the factors that affect happiness and found that they are mainly related to management support, organizational culture and human resource management (HRM) practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if such an employee were to score high on CRI, he or she may personalize any feedback regarding the value of creativity (Farmer et al , 2003): the perceived risks go beyond the loss of tangible rewards; it entails a potential loss of self and identity. A study by Al Hosani et al (2021) with (senior) managers from different public service organizations in the United Arab Emirates pointed to an individual’s creative self-efficacy and risk-taking as strong determinants for an employee’s IWB. Thus, if public-sector employees are motivated to develop the necessary skills and are inspired to change and learn, they are more likely to engage in IWB (Al Hosani et al , 2021; Mutonyi et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As demands for more efficient delivery of public services grow (Ibrahim and Al Falasi, 2014), so does the pressure for public sector employees to be innovative in their work behavior. By integrating relevant constructs from the organizational/management literature, such as prosocial job characteristics, we enhance the theoretical understanding of public sector innovation (Al Hosani et al, 2023;Houtgraaf, 2022) and offer practical insights. While we did not explore the consequences of IWB in this study, its potential impact on enhancing the value and delivery of public services is well-documented (Bani-Melhem et al, 2018).…”
Section: Job Impact and Employee Innovative Behaviormentioning
confidence: 99%